Serosurvey for selected infectious agents in two sympatric species of cormorants (Phalacrocorax atriceps and Phalacrocorax magellanicus) from coastal Patagonia, Argentina - Gallo, Luciana; Quintana, Flavio Roberto; Uhart, Marcela (Journal of Wildlife Diseases)
We conducted a serologic survey for selected infectious agents on two sympatric cormorants, the Imperial Cormorant (Phalacrocorax atriceps) and the Rock Shag (Phalacrocorax magellanicus). Blood was collected from 267 Imperial Cormorants and 106 Rock Shags at 17 colonies along the Patagonia Atlantic shore during nine breeding seasons (1994, 1999?2001, 2005? 2008, 2010). Antibodies to four pathogens were common to both species and frequently observed: avian paramyxovirus type 1 (56.2% of Imperial Cormorants and 55.8% of Rock Shags); avian adenovirus (67.3% of Imperial Cormorants and 40.2% of Rock Shags); infectious bronchitis virus serotypes IBV-41, IBV-46, IBV-99, and IBV-JMK (52.5% of Imperial Cormorants and 63.9% of Rock Shags); and Salmonella pullorum (17.7% of Imperial Cormorants and 6.6% of Rock Shags). Antibody prevalence for these pathogens varied significantly between species, except for avian paramyxovirus type 1. Exposure to avian paramyxovirus type 1 and all serotypes of infectious bronchitis virus varied significantly among seasons in both species. In contrast, the sporadic occurrence of positive titers suggest that cormorants had occasional exposure to Aspergillus spp. (3.3% of Rock Shags, only in 2000), avian paramyxovirus type 3 (4.8% of Rock Shags, only in 2008), Chlamydophila spp. (0.8% of Imperial Cormorants, only in 2010), and avian reovirus (1.1% of Rock Shags, only in 1999; 29.4% of Imperial Cormorants, in 2008 and 2010). Both species were antibody negative for avian encephalomyelitis virus, avian influenza virus, avian laryngotracheitis virus, avian paramyxovirus type 2, and infectious bursal disease virus. We provide the first information on pathogen exposure, indicated by detection of antibody in blood samples, for two sympatric species of South Atlantic cormorants. To determine major causes of morbidity and mortality in these birds future efforts should focus on necropsy surveys in cormorant colonies. Fil: Gallo, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. ...